A Philosophical Approach to Business Education - Woiceshyn, Jaana (Canadian Journal of Higher Education, 1992)
Business education has been blamed for deficiencies in the leadership, decision- making and ethical conduct of business managers. The quantitative and analytical orientation in business school curricula and the consequent lack of humanities-based courses have been identified as reasons. The fundamental reason, however, lies in the philosophy of business research and education which shapes the curricula, teaching methods, and ultimately the graduates' ability to handle various managerial functions. The most commonly recognized philosophical basis of business research is empiricism. The argument presented here is that pragmatism, which shares elements with empiricism, has also significantly shaped business education. This paper is an attempt to show why empiricism, together with pragmatism, are the root causes of the above deficiencies. Supplementing business school curricula with humanities courses, a strategy often recommended to correct for the deficiencies, is not sufficient. As an alternative solution, an objective philosophical approach is evaluated, along with its practical implications for business education.